2015
DOI: 10.1371/journal.pone.0139308
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length Is Not Related to Established Cardiovascular Risk Factors but Does Correlate with Red and White Blood Cell Counts in a German Blood Donor Population

Abstract: Telomere length (TL) is considered a marker of biological aging and has been associated with the presence of various coronary risk factors in patients. Much less is known about the relationships between TL and classic coronary risk factors in other populations. We measured TL in peripheral blood leukocytes of 343 middle-aged blood donors (mean age 40.2 ± 12.4 years; 201 men, 142 women) using quantitative polymerase chain reaction. Median TL was 0.86 (range: 0.48–1.85) relative TL units. In linear regression an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…[12][13][14][15][16][17] However, others have failed to replicate these findings. [18][19][20][21] For example, a study by Menke et al found no association between LTL and type 2 diabetes mellitus using the same NHANES data. 19 The reasons for these inconsistencies are not completely understood, but it is likely that LTL shortening is the result of the overall impact of multiple CVD risk factors working in tandem than a single CVD risk factor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14][15][16][17] However, others have failed to replicate these findings. [18][19][20][21] For example, a study by Menke et al found no association between LTL and type 2 diabetes mellitus using the same NHANES data. 19 The reasons for these inconsistencies are not completely understood, but it is likely that LTL shortening is the result of the overall impact of multiple CVD risk factors working in tandem than a single CVD risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported a significant association of shorter LTL with cigarette smoking, obesity, physical inactivity, poor diet, hypertension, and type 2 diabetes mellitus . However, others have failed to replicate these findings . For example, a study by Menke et al found no association between LTL and type 2 diabetes mellitus using the same NHANES data .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not observe any statistically significant association between LTL and other leukocyte counts, suggesting that shorter LTL is a reflection of bone marrow regenerative capacity rather than global circulating cellular reserve, although this issue remains controversial. 4248 …”
Section: Discussionmentioning
confidence: 99%
“…Within the current study, we also find shorter LTL is associated with a higher level of triglycerides (coefficient = −0.016, P = 0.041). Previous studies have demonstrated a mixed relationship between high triglyceride levels and shorter telomeres, with some studies demonstrating a significant relationship 41 42 , whereas other studies have not 43 44 . Interestingly, in a study of subjects with diabetes, the presence of the GG genotype of the -866G/A (rs659366) is associated with higher triglycerides (≥1.70 mM), total cholesterol (≥6.0 mM) and LDL-cholesterol (≥3.35 mM) levels in T2DM patients 45 .…”
Section: Discussionmentioning
confidence: 98%